Huge pelvi-abdominal malignant inflammatory myofibroblastic tumor with rapid recurrence in a 14-year-old boy - Lu, Chia-Hsun (Baishideng, 2010)
Inflammatory myofibroblastic tumor (IMT) is an uncommon benign neoplasm with locally aggressive behavior but malignant change is rare. We report an unusual case of pelvic-abdominal inflammatory myofibroblastic tumor with malignant transformation in a 14-year-old boy presenting with abdominal pain and 9 kg body weight loss in one month. Computed tomography revealed a huge pelvi-abdominal mass (30 cm), possibly originating from the pelvic extraperitoneal space, protruding into the abdomen leading to upward displacement of the bowel loops, downward displacement of the urinary bladder, massive central necrosis, a well-enhanced peripheral solid component with prominent peritumoral vascularity. Subsequent examination confirmed the computed tomographic findings. Histopathologic examination revealed proliferative epitheloid and spindle cells, inflammatory cell infiltration and high mitotic counts. Immunohistochemistry was strongly positive for anaplastic lymphoma kinase and revealed a high proliferative index (ki-67 = 40%). DNA sequencing and electronic microscopy further confirmed the primitive fibroblastic cell phenotype of the tumor and a final diagnosis of inflammatory myofibroblastic tumor with malignant transformation was established. Rapid tumor recurrence was noted 20 d after radical tumor resection. To our knowledge, this is the largest documented case of IMT in a pediatric patient and the first report of IMT with malignant transformation originating from the pelvic extraperitoneal space.